Rising Returns to Schooling in Argentina, 1992-2002 : Productivity or Credentialism? - Savanti, Maria Paula (World Bank, Washington, DC, 2012)
There has not been much change in the premium to primary education, while the returns to secondary education increased, but by less than the premium to university. The returns to incomplete university also increased significantly. There is a signal that there might be credentialism at the tertiary level, but 15 years of schooling also represents a significant threshold. The returns to schooling are higher in the private sector. There is little evidence of screening or credentialism driving the returns to schooling, which increased significantly in Argentina from 1992 to 2002.